Mice deficient in dihydrolipoyl succinyl transferase show increased vulnerability to mitochondrial toxins - Lichuan Yang; Qingli Shi; Daniel J. Ho; Anatoly A. Starkov; Elizabeth J. Wille; Hui Xu; H.L. Chen; Steven Zhang; Cliona M. Stack; Noel Y. Calingasan; Gary E. Gibson; M. Flint Beal (Neurobiology of Disease, 2009)
The activity of a key mitochondrial tricarboxylic acid cycle enzyme, α-ketoglutarate dehydrogenase complex (KGDHC), declines in many neurodegenerative diseases. KGDHC consists of three subunits. The dihydrolipoyl succinyl transferase (DLST) component is unique to KGDHC. DLST+/− mice showed reduced mRNA and protein levels and decreased brain mitochondrial KGDHC activity. Neurotoxic effects of mitochondrial toxins were exacerbated in DLST+/− mice. MPTP produced a significantly greater reduction of striatal dopamine and tyrosine hydroxylase-positive neurons in the substantia nigra pars compacta of DLST+/− mice. DLST deficiency enhanced the severity of lipid peroxidation in the substantia nigra after MPTP treatment. Striatal lesions induced by either malonate or 3-nitropropionic acid (3-NP) were significantly larger in DLST+/− mice than in wildtype controls. DLST deficiency enhanced the 3-NP inhibition of mitochondria enzymes, and 3-NP induced protein and DNA oxidations. These observations support the hypothesis that reductions in KGDHC may impair the adaptability of the brain and contribute to the pathogenesis of neurodegenerative diseases.